Peningkatan keterampilan menulis karangan narasi melalui model pembelajaran kooperatif tipe scramble kelas III sekolah dasar - Selfiana Coo; Retno Winarni; Yulianti Yulianti (Universitas Sebelas Maret, 2019)
The purpose of this study is to improve writing skills through learning scramble cooperative type in Grade III stundentsof Laweyan Primary School No.54 Surakarta Academic Year 2018/2019. The subject of this research were on classroom include teacher 35 students. The use of data were collected through observation, interview, tes and documention techniquers. The analysis data consist ofcollection data, reduction data, presentation data, and tge canclusions. The results of this study is indicate that in the acquisition value of the average narrative writing essay skills are 56.51 with a 8.57% classical completeness. In the first cycle, the average score increased to 65.47 with a classical completeness of 48.57%, while in the second cycle the average score was 74.82 with a 88.57% classical completeness. Based on the results of the research obtained, it shows that learning model scramble cooperative type can improve the narrative essay writing skills in grade III students of Laweyan No. SD Negeri. 54 Surakarta Academic Year 2018/2019.